Ethical AI in Public Administration: Ensuring Transparency and Trust in Governance Systems (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
Artificial Intelligence (AI) is rapidly transforming public administration, from decision-making to service delivery. Governments across the world are adopting AI tools for predictive governance, citizen engagement, and policy design. However, the ethical implications of these technologies—such as bias, surveillance, and lack of transparency—pose significant challenges. This paper investigates the ethical dimensions of AI in public governance, focusing on transparency, accountability, and citizen trust. Using a mixed-methods approach, the research analyzes government AI projects in India, the UK, and Estonia, supported by primary survey data. The study finds that while AI improves efficiency, ethical governance frameworks remain underdeveloped, leading to concerns over fairness and data privacy. The paper proposes a model for Ethical AI Governance (EAIG) that integrates algorithmic transparency, citizen participation, and institutional accountability.